Fostering Sound Financial Sector Development - World Bank (Washington, DC, 2014)
This note outlines a short, to medium-term reform agenda to foster sound financial sector development. Mexico needs to broaden and deepen its financial system without compromising the financial stability gains of the last decade. Much more private investment is needed to transform the economy to boost productivity, and despite improvements in recent years, many households and firms still lack adequate access to financial services. Using the financial payments system to promote financial inclusion is a sound way to broaden access. However, experience in several countries has shown that accelerated (or forced) expansion of credit can harm rather than benefit customers. If financial institutions do not follow sound practices, they can fail, harming borrowers and depositors alike and creating social unrest. Institutional failures may also lead to costly bailouts, with substantial fiscal cost. An oversight system (both micro, and macro, prudential) that encourages prudent-risk taking and facilitates prompt resolution of failed institutions ensures that strategies for financial deepening do not compromise financial stability.